Peran SAARC dalam Konflik Persengketaan Wilayah Kashmir antara India dan Pakistan - Nugroho, Athallah Dhiwabimo; Santoso, Made Panji Teguh; Gustianti, Nurbani Adine (Peneliti.net, 2025)
The Kashmir dispute involves two major countries, India and Pakistan, and has a disruptive effect on the South Asian region. As a regional international organization that oversees the South Asian region, SAARC participates in efforts to resolve conflicts that occur in its members, namely India and Pakistan. In its efforts SAARC takes a role in two ways, namely as a mediator and facilitator. As a neutral actor or third party SAARC helps mediate India and Pakistan in conducting a peaceful dialog that aims to resolve disputes between the two countries. Taking on the role of facilitator, SAARC holds an annual meeting called the SAARC Summit to negotiate efforts to resolve the conflict in Kashmir. However, SAARC has yet to find a solution to the Kashmir conflict. Even so, SAARC as the only international organization in the South Asian region continues to try and find ways so that the dispute between India and Pakistan can be resolved soon.